2014
DOI: 10.1007/s00425-014-2115-1
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous salicylic acid accumulation is required for chilling tolerance in cucumber (Cucumis sativus L.) seedlings

Abstract: Salicylic acid (SA) is an important plant hormone, and its exogenous application can induce tolerance to multiple environmental stresses in plants. In this study, we examine the potential involvement of endogenous SA in response to chilling in cucumber (Cucumis sativus L.) seedlings. A low temperature of 8 °C induces a moderate increase in endogenous SA levels. Chilling stimulates the enzymatic activities and the expression of genes for phenylalanine ammonia-lyase (PAL) and benzoic acid-2-hydroxylase rather th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(80 citation statements)
references
References 54 publications
5
75
0
Order By: Relevance
“…Furthermore, although the number of studies is still very limited for plants in their natural habitat, highmountain plants tend to accumulate large amounts of ABA (Bano et al, 2009), a phytohormone that is known to mediate the acclimation/adaptation of plants to temperature extremes by modulating the up-and down-regulation of numerous genes (Gilmour and Thomashow, 1991). The activation of other chemical defenses, such as the accumulation of salicylates and jasmonates, which serve against biotrophs and necrotrophs, can also be affected by extreme temperatures (Kosova et al, 2012;Dong et al, 2014;Miura and Tada, 2014), but it has not been investigated thus far in high-mountain plants.…”
mentioning
confidence: 99%
“…Furthermore, although the number of studies is still very limited for plants in their natural habitat, highmountain plants tend to accumulate large amounts of ABA (Bano et al, 2009), a phytohormone that is known to mediate the acclimation/adaptation of plants to temperature extremes by modulating the up-and down-regulation of numerous genes (Gilmour and Thomashow, 1991). The activation of other chemical defenses, such as the accumulation of salicylates and jasmonates, which serve against biotrophs and necrotrophs, can also be affected by extreme temperatures (Kosova et al, 2012;Dong et al, 2014;Miura and Tada, 2014), but it has not been investigated thus far in high-mountain plants.…”
mentioning
confidence: 99%
“…Another important ROS resource is NADPH oxidase. However, accumulating evidence has suggested that SA-mediated ROS production is independent of NADPH oxidase [25, 57]. Here, the SA-induced ROS was concluded to be generated from the imbalance between the photosynthetic electron transport and carbon fixation reaction, and this conclusion was confirmed by the light-dependency of ROS generation (Fig 4).…”
Section: Discussionmentioning
confidence: 59%
“…The quantitative determination and diaminobenzidine (DAB) histochemical staining of H 2 O 2 in cucumber leaves was performed as described previously [25]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations